Managing alcohol-related attendances in emergency care: can diversion to bespoke services lessen the burden?. Issue 2 (28th November 2017) - Irving, Andy; Goodacre, Steve; Blake, Joanne; Allen, Davina; Moore, Simon C
Abstract : Acute alcohol intoxication (AAI) has a long history of burdening emergency care services. Healthcare systems around the world have explored a variety of different services that divert AAI away from EDs to better manage their condition. Little formal evaluation has been undertaken, particularly in the UK where alcohol misuse is one of the highest in the world. In this article, we outline a brief history of diversionary services, introduce the concept of Alcohol Intoxication Management Services (AIMS) and describe examples of AIMS in the UK. We then describe Evaluating the Diversion of Alcohol-Related Attendances, a natural experiment including six cities with AIMS compared with six cities without, that involves an ethnographic study, records patient experiences in both AIMS and EDs, assesses impact on key performance indicators in healthcare and evaluates the cost-effectiveness of AIMS.